E-Learning Post Stroke Rehabilitation: Systematic Review - Dwiyanto, Yusup; Luanda, Desi; Fredy, Muhammad Khalid; Firdaus, Nuzula; Lusiana, Lusiana; Desy, Kemala; sofiani, Yani (Journal of Global Research in Public Health, 2021)
Background: Stroke is the biggest cause of death after heart attack and has an impact on disability that can reduce the quality of life. Disability due to stroke is the result of damage to motor, sensory and cognitive functions of the patient. For this reason, there is a need for rehabilitation that can repair the damage to this function. Rehabilitation in stroke patients can be combined with technological advances. This will have a good impact on the rehabilitation program for stroke patients. The purpose of this study was to provide knowledge about post-stroke rehabilitation programs using electronic learning programs. Methods: This research design uses a systematic review approach by collecting several articles from a data base published in 2011-2020. The article search was conducted by entering the keywords stroke rehabilitation audiovisual, stroke rehabilitation video, stroke rehabilitation system, and stroke rehabilitation telecommunications. Article searches have predefined inclusion and exclusion criteria. Inclusion criteria included patients diagnosed with stroke. The research design was a randomized control trial and experimental research. Exclusion criteria included stroke patients who were being hospitalized. Result: The results of a database search obtained 9,409 articles, from Pubmed 379 articles, Proquest 7,640 articles, and Google Scholar 1,390 articles. After sorting with predetermined criteria, 6 articles were found that matched. Conclusion: The conclusion in this study was that the post-stroke rehabilitation e-learning program gave significant results in improving motor, sensory and cognitive functions of patients in living their daily lives.